Acquired resistance of melanoma cells to the antineoplastic agent fotemustine is caused by reactivation of the DNA repair gene mgmt - Christmann, Markus; Schadendorf, Dirk (International journal of cancer, 2001)
Acquired resistance to antineoplastic agents is a frequent obstacle in tumor therapy. Malignant melanoma cells are particularly well known for their unresponsiveness to chemotherapy; only about 30% of tumors exhibit a transient clinical response to treatment. In our study, we investigated the molecular mechanism of acquired resistance of melanoma cells (MeWo) to the chloroethylating drug fotemustine. Determination of O6-methylguanine-DNA methyltransferase (MGMT) activity showed that MeWo cells that acquired resistance to fotemustine upon repeated treatment with the drug display high MGMT activity, whereas the parental cell line had no detectable MGMT. The resistant cell lines exhibit cross-resistance to other O6-alkylating agents, such as N-methyl-N′-nitro-N-nitrosoguanidine. Acquired resistance to fotemustine was alleviated by treatment with the MGMT inhibitor O6-benzylguanine demonstrating that reactivation of MGMT is the main underlying cause of acquired alkylating drug resistance. As compared with control cells, both MGMT mRNA and MGMT protein were expressed at a high level in fotemustine resistant cells. Southern blot analysis proved that the MGMT gene was not amplified. There was also only an insignificant difference in the CpG methylation pattern of the MGMT promoter whereas a clear hypermethylation in the body of the gene was observed in fotemustine resistant cells. The conclusion that hypermethylation is responsible for reactivation of the MGMT gene gained support by the finding that MGMT activity significantly declined and cells reverted (partially) to the parental sensitive phenotype upon treatment with 5-azacytidine. This is the first report of acquired resistance to a chloroethylating antineoplastic drug of melanoma cells due to gene hypermethylation.